METHODOLOGICAL PRINCIPLES OF THE FUNCTIONING OF MECHANISMS FOR RESPONSE TO CRISIS SITUATIONS THREATENING THE NATIONAL SECURITY OF UKRAINE - Yevtushenko, Ihor (Honor and Law, 2023)
The article proves that the complex socio-political and military situation that has developed in Ukraine today has a direct impact on the state of ensuring national security. Crisis situations that threaten national security require a comprehensive solution, as well as the participation of various departments, government structures and organizations in ensuring the safety of citizens, protecting the constitutional order, sovereignty and territorial integrity of the state, in eliminating grave consequences, etc. Under such conditions, mechanisms for responding to crisis situations that threaten the national security of Ukraine play an important role, and therefore, the issue of researching the methodological foundations of the functioning and development of mechanisms for responding to crisis situations that threaten the national security of Ukraine is currently relevant. It was established that in modern society, management mechanisms play the main role in the state policy of responding to crisis situations that threaten national security. Mechanisms of state administration are supposedly "management tools" in the state system. Today, the scientific community has provided a significant number of options for defining the concept of control mechanisms. Mechanisms for responding to crisis situations that threaten national security should be understood as a set of special measures, means, levers, incentives, with the help of which the security and defense forces are involved and act to resolve extreme exacerbations of contradictions, acute destabilization of the situation in any field of activity, region, country. It was determined that the study of the methodological principles of the functioning of the mechanisms for responding to crisis situations that threaten the national security of Ukraine should be based on the definitions of the mechanisms of public administration in the broad sense and include three stages: analysis, development of the theoretical aspect; organizational aspect, development of a methodological basis; checking for adequacy in the national security system. The peculiarity of the methodological approach to the functioning of the mechanisms for responding to crisis situations that threaten the national security of Ukraine specified in the article is the actualization of the implementation of civil control by citizens and public associations in the system of ensuring national security in response to crisis situations both at the national and regional and local levels. This approach maintains the direction of the development of mechanisms for responding to crisis situations that threaten the national security of Ukraine. Therefore, in further scientific research, it is necessary to substantiate the proposals for solving the scientific problem regarding the development of mechanisms for responding to crisis situations that threaten the national security of Ukraine.